pH-Responsive mesoporous silica nanoparticle-reinforced composite resin with remineralization capability - Ge, Yongcheng; Zhao, Ting; Liu, Yuguang; Fan, Sizheng; Liu, Pengyuan; Zhao, Chengji; Liu, Xiaoqiu (BMC oral health, 2025)
Enhancing the mechanical properties of composite resins and promoting dentin remineralization are effective strategies for extending the longevity of restorations. In this study, we developed a pH-responsive composite resin reinforced with phosphorylated chitosan (Pchi)/amorphous calcium phosphate (ACP) and amino-functionalized mesoporous silica nanoparticles (MSNs) (Pchi/ACP@A-MSN complexes). MSNs and Pchi/ACP were synthesized, and the resulting composite resins were classified into five groups based on the filler compositions: Group A (45wt.% A-MSNs + 15wt.% Pchi/ACP + 40wt.% resin matrix), Group B (22.5wt.% A-MSNs + 37.5wt.% Pchi/ACP@A-MSNs + 40wt.% resin matrix), Group C (45wt.% nonporous silica + 15wt.% Pchi/ACP + 40wt.% resin matrix), Group D (15wt.% Pchi/ACP + 85wt.% resin matrix), and Group E (100wt.% resin matrix). The degree of double-bond conversion and mechanical properties (Flexural modulus, flexural strength, and Vickers hardness) of each group were measured. The remineralization performance and calcium ion (Ca²⁺) release performance were observed. Cell viability was evaluated by CCK-8 assay. Group A exhibited the highest mechanical performance, with flexural strength of 115 ± 9.68 MPa, flexural modulus of 5.99 ± 0.44 GPa, and Vickers hardness of 31.73 ± 2.39 HV. All groups achieved double-bond conversion rates > 50% after 60 s of light curing (P > 0.05). At pH 4.0, Group B exhibited the highest Ca²⁺ release (276 µg/mL), while Group D had the highest release at pH 7.4 (128 µg/mL). SEM and EDS analyses indicated that Group D achieved the most substantial dentin remineralization, followed by Groups C and A. All groups maintained cell viability above 75% throughout the 7-day assay, with no significant cytotoxicity observed. A composite formulation containing 45 wt% A-MSNs and 15 wt% Pchi/ACP (Group A) significantly enhanced mechanical strength. The 15 wt% Pchi/ACP formulation (Group D) demonstrated the greatest remineralization effect. Group B, combining A-MSNs and Pchi/ACP@A-MSNs, provided pH-responsive Ca²⁺ release with a favorable balance of mechanical performance and remineralization potential. All formulations met the biocompatibility requirements for dental applications.